PD-1 expression identifies proliferating malignant CLL B cells and is a potential biomarker of response to BTK inhibitor therapy - Andres Chang; Adam N. Pelletier; Donald J. McGuire; Maria Tsagiopoulou; Maria Karipidou; Amy Ayers; Alyssa M. K. Leal; Michael C. Churnetski; Colin B. O’Leary; Jeffrey M. Switchenko; Carl Davis; David A. Frank; et al. (Proceedings of the National Academy of Sciences, 2025)
Chronic lymphocytic leukemia (CLL) remains incurable despite treatment advances, and a major challenge is that biomarkers that predict response and resistance to current therapies are lacking. We report that activated and proliferating malignant CLL B cells in circulation express PD-1, a protein normally expressed in T cells. PD-1 expression is absent in circulating B cells from healthy controls and nonmalignant B cells from patients with CLL. Circulating PD-1 + CLL cells are found in all treatment naïve patients, regardless of immunoglobulin heavy-chain variable region gene mutation status or cytogenetic abnormalities. PD-1 + CLL cells are transcriptionally distinct compared to PD-1 − CLL cells and upregulate genes associated with cell activation, proliferation, and B cell receptor (BCR) and toll-like receptor (TLR) signaling. Indeed, ex vivo stimulation of the BCR and TLR9 readily increased PD-1 expression in CLL cells from treatment-naïve patients within 24 h, an effect that was blocked by Bruton’s tyrosine kinase inhibitors (BTKi). More importantly, patients initiating BTKi therapy experienced profound reductions in circulating PD-1 + CLL cell numbers within 1 mo, which is in line with reduction in Ki-67 + CLL cells. Elevated percentages of circulating PD-1 + CLL cells also preceded a clinical diagnosis of disease progression in patients receiving BTKi. Thus, our findings indicate that PD-1 expression is a potential biomarker to identify proliferating CLL cells in vivo and will be useful to predict response and resistance to BTKi. In addition, eliminating PD-1 + CLL cells with depleting anti-PD-1 monospecific or bispecific antibodies should be explored as a potential therapeutic strategy.